2010
DOI: 10.1590/s1519-69842010000400012
|View full text |Cite
|
Sign up to set email alerts
|

Cold fronts and reservoir limnology: an integrated approach towards the ecological dynamics of freshwater ecosystems

Abstract: In this paper the authors discuss the effects of cold fronts on the dynamics of freshwater ecosystems of southeast South America. Cold fronts originating from the Antarctic show a monthly frequency that promotes turbulence and vertical mixing in reservoirs with a consequence to homogenize nutrient distribution, dissolved oxygen and temperature. Weak thermoclines and the athelomixis process immediately before, during and after the passage of cold fronts interfere with phytoplankton succession in reservoirs. Cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 13 publications
5
39
0
3
Order By: Relevance
“…The most critical events, with a density of cyanobacteria of more than 30000 cel/mL, were related to the Instability Line (34324.5 cel/mL) and to the Stationary Polar Atlantic Front (37761.9 cel/mL). These results demonstrate that the mechanism of mixing and stratification proposed by Tundisi et al (2010) could occur both with the front enters and also with other weather types that disturb the water column. Within this context, the successions of weather types which cause the increase in the cyanobacterial density are mainly related to a meeting of a Tropical Equatorial mass or Equatorial Continental mass with a Tropical Instability Line or Polar Atlantic Front and its derivations.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…The most critical events, with a density of cyanobacteria of more than 30000 cel/mL, were related to the Instability Line (34324.5 cel/mL) and to the Stationary Polar Atlantic Front (37761.9 cel/mL). These results demonstrate that the mechanism of mixing and stratification proposed by Tundisi et al (2010) could occur both with the front enters and also with other weather types that disturb the water column. Within this context, the successions of weather types which cause the increase in the cyanobacterial density are mainly related to a meeting of a Tropical Equatorial mass or Equatorial Continental mass with a Tropical Instability Line or Polar Atlantic Front and its derivations.…”
Section: Resultsmentioning
confidence: 62%
“…The vertical structure of tropical reservoirs is susceptible to stratification and the mixing process originating from weather events, as documented in Tundisi et al (2004Tundisi et al ( , 2010 and Moraes et al (2010). These studies showed that, according to the variability of wind stress and regimes, aquatic ecosystems present several responses in their physical, chemical, and biological variables.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Weather conditions such as precipitation, wind and cold front play important roles over the water column mixing (Curtarelli et al 2014) and, consequently, underwater light climate (Tundisi et al 2010). The water column mixing and retention time are pointed as the main responsible for phytoplankton species richness in the reservoir (Calijuri et al 1996;Matsumura-Tundisi and Tundisi 2005;Dellamano-Oliveira et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The water column mixing and retention time are pointed as the main responsible for phytoplankton species richness in the reservoir (Calijuri et al 1996;Matsumura-Tundisi and Tundisi 2005;Dellamano-Oliveira et al 2008). On the other hand, predominance for determined specie is frequently associated with thermal stratification and stability of the water column (Tundisi et al 2010). Therefore, blooms of cyanobacteria occur in the fall when retention time is longer, while chlorophyta and diatom are more common during the spring and summer when the retention time is shorter (Perry et al 1990;Lepš et al 1990).…”
Section: Introductionmentioning
confidence: 99%